Hemostasis parameters as prognostic biomarkers in gynecological cancer patients - E. V. Slukhanchuk; V. O. Bitsadze; A. G. Solopova; J. Kh. Khizroeva; J.-C. Gris; I. Elalamy; D. V. Shcherbakov; A. S. Shkoda; L. L. Pankratyeva; J. Yu. Ungiadze; L. A. Ashrafyan; A. D. Makatsariya (IRBIS LLC, 2023)
Hypercoagulation is a typical condition for cancer patients. In addition, various arms of the hemostasis system become involved in tumor growth, invasion, metastasis, neoangiogenesis as well as immunoevasion. The magnitude of activated hemostasis is driven by tumor phenotype. Parameters characterizing coagulation, intensity of fibrinolysis processes, platelet aggregation and activation as well as endothelial activation mirror magnitude of hemostasis activation in oncological process, but may also be considered as candidate markers of tumor progression and predictors of oncological diseases outcome. This review summarizes the study data assessing a value of predictive hemostasis biomarkers for overall survival and response to therapy in oncogynecology and mammology. The most promising biomarkers have been identified and used in the future for risk stratification as well as personalized patient management.